Intergenerational and Intercultural Differences in Work Values in Quebec and the United Arab Emirates - Wils, Thierry; Saba, Tania; Waxin, Marie-France; Labelle, Christiane (Relations industrielles / Industrial Relations, 2011)
The purpose of this research is to examine whether differences exist in the work values of several generations among 186 respondents in Quebec and 252 Arab respondents in the United Arab Emirates. We used an abridged version of Wils, Luncasu and Waxin (2007) work value inventory, including 28 work values arranged on four poles: self-enhancement, self-transcendence, openness-to-change and conservation. In the Quebec sample, there were no significant differences between generations in their scores on the four work value poles. In the Arab sample, the younger generation attached less importance to self-enhancement, but more importance to self-transcendence than the older generation with a small effect size. Our results also demonstrate that cultural origin had no significant impact on the average score on the work value poles. The diversity in work values among generations and cultures that we found in our samples does not support the idea that human resource management practices should be adjusted for different generations.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Comparative studies; Generations; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Work ethic